The Effect of Ergonomic Gymnastics “Kandiha Weki” on Foot Sensivity And Sugar Levels in DM Patients In The Working Area of East Bolo Community Health Center (International Journal of Scientific Research and Management (IJSRM), 2025)
Diabetes mellitus is a hyperglycemic disease characterized by the absolute absence of insulin or a relative decrease in cell insensitivity to insulin. Type 2 DM constitutes 90% of all diabetes mellitus categories. Diabetes mellitus is a fairly high cause of death, due to complications that cause atherosclerosis, coronary heart disease and stroke. The research design was quasi-experimental, using a pre-test and post-test with control group design. Using Wilcoxon and Mann Whitney tests. The sampling technique was purposive sampling with a sample of 100 respondents. The results of data analysis using the Wilcoxone test in the treatment group showed a p-value of 0.000 (p<0.05) for the knowledge, attitude and behavior variables. In the control group, a p-value was obtained of 0.002 (p<0.05) in the knowledge variable, a p-value was obtained of 0.001 (p<0.05) in the attitude variable, a p-value was obtained of 0.001 (p<0.05) on behavioral variables. These results show that Ha is accepted and H0 is rejected, so it can be interpreted that there is an influence of providing video media and modules on increasing knowledge, attitudes and behavior in an effort to prevent complications. The results of the analysis in the intervention group and control group using the Mann Whitney Test, obtained ap value of 0.000 < 0.002, which indicates that the provision of video educational media in the intervention group was more significant in increasing knowledge. The results of statistical tests on attitudes in the intervention group and control group showed ap value of 0.000 < 0.001, which indicates that the provision of video educational media in the intervention group was more significant in improving respondents’ attitudes. And the results of statistical behavioral tests in the intervention group and control group showed ap value of 0.000 < 0.001, which shows that the provision of video educational media in the intervention group was more significant in improving behavior. It can be concluded that video education media and modules have an influence in increasing knowledge, attitudes and behavior, but providing education using videos is more significant in increasing knowledge, attitudes and behavior in type 2 diabetes mellitus.